SPECIFIC FEATURES OF SELECTING ORGANIZATIONAL DEVELOPMENT STRATEGIES IN THE CONTEXT OF DIGITAL TRANSFORMATION - Sobirjonov Samandar Murodil ugli; Yusupov Ulugbek (TADQIQOTLAR, 2026)
Abstract Digital  transformation  has  fundamentally  altered  the  competitive  landscape within which enterprises formulate and execute organizational development strategies. This  article  examines  the  specific  features  that  distinguish  strategy  selection  under digital  disruption  from  conventional  pre-digital  paradigms.  Drawing  on  classical frameworks  -  including  the  Resource-Based  View,  Dynamic  Capabilities  theory, Porter's Generic Strategies, and the Balanced Scorecard - the article develops a five-stage Digital Strategy Selection Model and a Digital Strategy Positioning Matrix. The analysis is grounded in empirical data from Uzbekistan's tourism sector, with reference to 'SKY LUX TRAVEL' LLC, whose 791.8% revenue growth between 2022 and 2024 illustrates how digital capabilities generate sustained competitive advantage.